Diffuse axonal injury: a case report and MRI findings - Duc Tan Vo, PhD. MD (Elsevier, 2022)
Diffuse axonal injury (DAI) is one of the most severe types of primary traumatic brain injury. In recent years, MR imaging has been gaining popularity as an adjunctive imaging method in patients with DAI. In this case report, we describe MRI findings of an 11-year-old male patient diagnosed with DAI and discuss the role of different sequences in the evaluation of DAI.